ROLE OF PULMONARY HYPERTENSION IN THE DEVELOPMENT OF CIRRHOTIC CARDIOMYOPATHY - M. V. Chistyakova; A. V. Govorin; E. V. Radaeva (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To investigate the presence of pulmonary hypertension (PH) in patients with viral liver cirrhosis (LC) and its impact on some indicators of portal hemodynamics, and echocardiographic parameters.Material and methods. The study included 95 patients with viral LC. The median age was 41.7 [33.2;46] years, median disease duration – 3.9 [2.6;6.9]-years. Group 1 consisted of 72 patients without PH – systolic pulmonary arterial pressure (SPAP)<30 mm Hg., group 2 – 23 patients with SPAP3139 mm Hg., control group included 19 healthy subjects. Doppler echocardiography (DEchoCG) and tissue DEchoCG were performed, and diameter,-mean flow velocity in the portal and inferior vena cava were measured.Results: PН was diagnosed in 24% patients with LC who had the enlargement diameter of portal, inferior vena cava veins, and reduced mean blood-flow velocity in the portal vein (p<0.001). According to the DEchoCG data, in patients with LC without PH, left ventricular remodeling occurs with an-increase in its mass and systolic volume; pulmonary artery dilatation and diastolic ventricular dysfunction are also revealed in comparison with the control-group (p<0.001). The revealed abnormalities especially increased in patients with PH, they also showed dilatation of the left atrium and decrease-in the contractility of ventricular myocardium (p <0.001). In patients with LC complicated by PH, a strong correlation was found between the diameter-of the portal vein and blood flow velocity in pulmonary artery (r=0.65, p<0.05), between the diameter of the inferior vena cava and right ventricle-rapid filling flow (r=0.93, p<0.05), between the diastolic function of the right ventricle (E/A) and the blood flow velocity in the portal vein (r=0.73;-p<0.05). The revealed correlations testify to high probability of development of collateral circulation – portal-pulmonary anastomoses.Conclusion: Detected hemodynamic disorders in viral LC indicate an important role of PH in the development of cirrhotic cardiomyopathy.Keywords: heart, рulmonary аrtery, cirrhosis of the liver.